A ESCOLA INCLUSIVA ESTÁ POSTA, E AGORA? - ARAUJO , KÊNIA VIRGINIA SILVA (2015)
The school environment is very rich in stories, moments, learning and experiences. Every teacher always has a lot to tell. The diversity of people in this universe makes us have a school daily life without routines, without limits for creativity. When faces with something new or unexpected, the teacher seems to transform himself in an innovative agent, conquer space, the situation, in order to dominate it and in varied opportunities, amaze us with enriching strategies. In this research, we have the opportunity of sharing unique and singular experiences that allowed us to contribute to the existing ones in the pedagogical field with students with special educational needs. Frustrating experiences also occur in the school environment; however, in the seeking to give voice to the teacher who develops the specialized educational service, we report here successful experiences. Then, with this, we report the contribution of a private school that has as one of its goals, education for all.